AN ASSESSMENT OF IFRS REGULATION FRAMEWORK: IMPLICATION FOR PRESENTATION OF FINANCIAL REPORTS AND FINANCIAL INFORMATION USEFUL IN NIGERIA - Oyasor, Emmanuel Imuede (J-MACC : journal of management and accounting, 2024)
Accounting regulations specify how companies should maintain records, pertaining to reported income and expenses, to accomplish some goals. In recent times, accounting standards have taken the form of International Financial Reporting Standards (IFRS) - a set of high-quality standards introduced by the International Accounting Standards Board (IASB) in 2001. This investigates the compliance of private in Nigeria on the framework of IFRS regulations. The paper applied the Chi-square to analyst responses from 200 respondents, including accountants and managers, from private in Nigeria. The paper revealed that there is a relationship between IFRS framework and the preparation and presentation of financial reports. Morso, there is a relationship between IFRS frameworks and financial information useful for evaluating performance.